Isolation, Characterization, and Tea Growth-Promoting Analysis of JW-CZ2, a Bacterium With 1-Aminocyclopropane-1-Carboxylic Acid Deaminase Activity Isolated From the Rhizosphere Soils of Tea Plants - Liu, Hui; Chen, Guang-Hui; Sun, Jing-Jing; Chen, Shu; Fang, Yong; Ren, Jia-Hong (Frontiers in Microbiology, 2022)
One of the major mechanisms underlying plant growth-promoting rhizobacteria (PGPR) is the lowering of ethylene level in plants by deamination of 1-aminocyclopropane-1-carboxylic acid (ACC) in the environment. In the present study, using ACC as the sole nitrogen source, we screened seven ACC deaminase-producing bacterial strains from rhizosphere soils of tea plants. The strain with the highest ACC deaminase activity was identified as Serratia marcescens strain JW-CZ2. Inoculation of this strain significantly increased shoot height and stem diameter of tea seedlings, displaying significant promotive effects. Besides, S. marcescens strain JW-CZ2 displayed high ACC deaminase activities in wide ranges of ACC concentration, pH, and temperature, suggesting the applicable potential of JW-CZ2 as a biofertilizer. Genome sequencing indicated that clusters of orthologous groups of proteins (COG) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways of JW-CZ2 mainly included amino acid transport and metabolism, transcription, carbohydrate transport and metabolism, inorganic ion transport and metabolism, and membrane transport. Moreover, genes in relation to phosphate solubilization, indole acetic acid (IAA) production, and siderophore were observed in the genome of JW-CZ2, and further experimental evidence demonstrated JW-CZ2 could promote solubilization of inorganic phosphate, inhibit growth of pathogenic fungi, and produce IAA and siderophore. These aspects might be major reasons underlying the plant growth-promoting function of JW-CZ2. Overall, this study provides a new S. marcescens strain, which has applicable potential as a promising biofertilizer.